THE PHOBIA CORONA (COVID 19) - WHAT WE CAN DO - Medani P. Bhandari (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The phobia Corona is spreading dynamically all over the world. The question is what we can do to stop this pandemic and what price we will have to pay for it. This opinion piece of ASEJ editorial team member Prof. Medani P. Bhandari addresses the really important issue that surrounds us today - the fear of infecting myself and my loved ones. Responsibility for the people we are in contact should be the key element. The overwhelming amount of information in the media, contributes to the deepening of fear about which the article deals. People need to be aware not only of the responsibility for the lives of others, they must also re-evaluate their own lives in such a way that money, power and material goods cease to occupy a higher priority than the supreme value of love and care for others. Currently, the world is slowing down and people are noticing their powerlessness in the face of nature. It can be assumed that Covid is one of the lessons that God is teaching us to protect us from ourselves.